PENGARUH EMPLOYER BRANDING, REPUTASI PERUSAHAAN, DAN E-RECRUITMENT TERHADAP MINAT GENERASI Z DALAM MELAMAR PEKERJAAN (STUDI PADA PT KERETA API INDONESIA) - Septiani Putri Pratama Murni; Sri Ekanti Sabardini (Juremi: Jurnal Riset Ekonomi, 2026)
This research aims to analyze the influence of employer branding, corporate reputation, and e-recruitment on Generation Z's interest in applying for jobs, with a case study at PT Kereta Api Indonesia (PT KAI). The study employed a quantitative survey method by distributing questionnaires to 112 respondents from Generation Z residing in Yogyakarta and interested in PT KAI. Multiple linear regression analysis results indicate that employer branding, corporate reputation, and e-recruitment variables have a positive and significant effect on job application interest, both partially and simultaneously. The Adjusted R Square value of 0.528 indicates that these three independent variables explain 52.8% of the variation in job application interest, while the remainder is affected by other factors not examined in this research. The findings highlight the importance of effective employer branding strategies, a strong corporate reputation, and an optimized e- recruitment system for organizations wishing to attract Generation Z job applicants. This study can serve as a reference for companies to design suitable recruitment approaches for the increasingly selective and digital-oriented young generation.